Implant loosening following THA with S-ROM prosthesis and subtrochanteric osteotomy: Three case reports - Ma, Yingkai; Ma, Xinnan; Cheng, Shi; Lv, Songcen; Qi, Xin (Frontiers in Surgery, 2023)
Prosthesis loosening after THA is a rather common complication. For DDH patients with Crowe IV, the surgical risk and complexity is significant. THA with S-ROM prosthesis combined with subtrochanteric osteotomy is a common treatment. However, loosening of a modular femoral prosthesis (S-rom) is uncommon in THA and has a very low incidence. With modular prostheses distal prosthesis looseness are rarely reported. Non-union osteotomy is a common complication of subtrochanteric osteotomy. We report three patients with Crowe IV DDH who developed prosthesis loosening following THA with an S-ROM prosthesis and subtrochanteric osteotomy. We addressed the management of these patients and prosthesis loosening as likely underlying causes.